Colorless tsukuru tazaki and his years of pilgrimage eaudiobook A novel. - Murakami, Haruki (Random House Audio, 2014)
INSTANT #1 NEW YORK TIMES BESTSELLER • One of the most revered voices in literature today gives us a story of love, friendship, and heartbreak for the ages. “Mesmerizing, immersive, hallucinogenic.”— Entertainment Weekly Colorless Tsukuru Tazaki and His Years of Pilgrimage is the remarkable story of a young man haunted by a great loss; of dreams and nightmares that have unintended consequences for the world around us; and of a journey into the past that is necessary to mend the present. ONE OF THE BEST BOOKS OF THE YEAR: The New York Times Book Review, The Washington Post, Financial Times, St. Louis Post-Dispatch, Slate, Mother Jones, The Daily Beast, BookPage *Années de pèlerinage (Years of Pilgrimage) - "Le mal du pays" by Franz Liszt, performed by Peter Mendelsund. Recorded by Charles Myers Recording Studio, Manhattan School of Music, The Gordon K. and Harriet Greenfield Hall. Kevin Boutote, Recording Engineer.